Creating a Buzz: Attracting Sci/Tech Students to the Library! - Mary Axford; Ray Bedner; Cathy Carpenter; Lori Critz; Leslie Madden; Brian Mathews; Crystal Renfro; Joanne Tobin (Issues in Science and Technology Librarianship, 2006)
In the land of the Georgia Tech Yellow Jackets, we are "swarming" the campus with a multi-targeted publicity campaign. The Library's newly formed Information Services Marketing Group has launched several dynamic initiatives in 2005 -- all in an effort to raise the profile of the Library, to increase gate count and resource usage, and to expand campus-wide partnership opportunities in a fast-paced urban environment. Shattering the image of the library as a book mausoleum, our new programs include Tuesday Talks, an afternoon speaker series spotlighting exciting campus research, and T-Paper, a hip, student-oriented restroom newsletter. Emerging projects include a stereotype-bursting library entry in the University's Homecoming Parade and posters of "STAR" student-athletes promoting library resources. The Marketing Group is meeting some key challenges facing today's academic science libraries, by fostering campus connections, creating new collaborative opportunities with faculty, and helping to rebrand our Library as a progressive 21st century "apiary." [ABSTRACT FROM AUTHOR]